New Reference PMHS Tests to Assess Whole-Body Pedestrian Impact Using a Simplified Generic Vehicle Front-End - Song, Eric; Petit, Philippe; Trosseille, Xavier; Uriot, Jerome; Potier, Pascal; Dubois, Denis; Douard, Richard (Stapp car crash journal, 2017)
This study aims to provide a set of reference post-mortem human subject tests which can be used, with easily reproducible test conditions, for developing and/or validating pedestrian dummies and computational human body models against a road vehicle. An adjustable generic buck was first developed to represent vehicle front-ends. It was composed of four components: two steel cylindrical tubes screwed on rigid supports in V-form represent the bumper and spoiler respectively, a quarter of a steel cylindrical tube represents the bonnet leading edge, and a steel plate represents the bonnet. These components were positioned differently to represent three types of vehicle profile: a sedan, a SUV and a van. Eleven post-mortem human subjects were then impacted laterally in a mid-gait stance by the bucks at 40 km/h: three tests with the sedan, five with the SUV, and three with the van. Kinematics of the subjects were recorded via high speed videos, impact forces between the subjects and the bucks were measured via load cells behind each tube, femur and tibia deformation and fractures were monitored via gauges on these bones. Based on these tests, biofidelity corridors were established in terms of: 1) displacement time history and trajectory of the head, shoulder, T1, T4, T12, sacrum, knee and ankle, 2) impact forces between the subjects and the buck. Injury outcome was established for each PMHS via autopsy. Simplicity of its geometry and use of standard steel tubes and plates for the buck will make it easy to perform future, new post-mortem human subject tests in the same conditions, or to assess dummies or computational human body models using these reference tests.